Macro- and micro- properties of multi-recycled aggregate concrete. (1st February 2020) - Thomas, C.; de Brito, J.; Cimentada, A.; Sainz-Aja, J.A.
Abstract: In a future scenario in which all the concrete is recycled concrete, it will be necessary to recycle the recycled concrete. However, it is known that the recycling of concrete implies a loss of properties. This paper shows an innovative technique, the computerized microtomograph, used to evaluate closed porosity, volume of limestone aggregate fraction and volume of mortar of the multi-recycled aggregate concrete, in order to answer the question: how many times it is possible to recycle concrete? First, the source concrete mix using limestone coarse and fine aggregates was characterized. This mix was crushed to obtain a recycled aggregate that was used to manufacture the 1st generation or current recycled aggregate concrete. After the characterization of this 1st generation concrete, and in the same way, a 2nd and a 3rd generation concrete were obtained and characterized, using recycled aggregates from the 1st and 2nd concrete generations respectively. The evaluation by computerized axial tomography allows to know how the successive recycled affect the properties of the concrete. The results show that it is possible to observe the distribution and quantify the aggregate, cement paste and closed porosity contents of the recycled aggregate concrete showing that 3rd generation recycled concrete shows almost twice as much mortar as 1st generation one and demonstrates that it is only possible to recycle the concrete a finite number of times.